Optimized Lysis-Extraction Method Combined With IS6110-Amplification for Detection of Mycobacterium tuberculosis in Paucibacillary Sputum Specimens - Kolia-Diafouka, Pratt; Godreuil, Sylvain; Bourdin, Arnaud; Carrère-Kremer, Severine; Kremer, Laurent; Van de Perre, Philippe; Tuaillon, Edouard (Frontiers in Microbiology, 2018)
Background: Nucleic acid tests offer powerful and promising tools to strengthen the potential of tuberculosis diagnosis assays. The sensitivity of molecular assays is critical for detection of Mycobacterium tuberculosis (MTB) in paucibacillary sputum. Material and Methods: The impact of targeting repetitive IS6110 sequences on the PCR sensitivity was evaluated across mycobacterium strains and reference material. Six lysis-extraction protocols were compared. Next, 92 clinical sputum specimens including 62 culture-positive samples were tested and the results were compared to sputum-smear microscopy, culture, and Xpert MTB/RIF test. Finally, the capacity to detect low Mycobacterium tuberculosis DNA concentrations was assessed in 40 samples containing <1.5 x102 copies/ml ex-vivo or after dilution. Results: The lower limit of detection using the IS6110 PCR was 107 genome copies/ml (95% CI: 83 - 130) using Mycobacterium tuberculosis H37Rv as a reference strain, versus 741 genome copies/ml (95% CI: 575-1094) using the senX3 PCR. The proportion of recovered Mycobacterium tuberculosis DNA after lysis and extraction ranged from 35% to 82%. The Chelex® method appeared as a more efficient protocol among the six different protocols tested. The sensitivity and specificity in clinical sputum samples were 95.1% (95% CI: 90.7-99.6) and 100% (95% CI: 96.2-100.8), respectively. Among 40 samples with low Mycobacterium tuberculosis DNA concentration, 75% tested positive for IS6110 PCR, versus 55% using the Xpert MTB/RIF assay (p= 0.03). Conclusion: Laboratory assays based on an efficient Mycobacterium tuberculosis lysis and DNA extraction protocols combined with amplification of IS6110 repeat sequences appear as a sensitive diagnostic method to detect MTB DNA in sputum with low bacterial load.